Consolidated list of indicators for assessing overall progress towards achievement of the targets referred to in paragraphs 9–10 of decision 2/CMA.5, and progress of the work on the indicators - United Nations Framework Convention on Climate Change (UNFCCC) Authors (2025)
This document provides an update on the progress of the experts convened by the Chairs of the subsidiary bodies to assist in the technical work under the United Arab Emirates–Belém work programme on indicators for measuring progress achieved towards the targets referred to in paragraphs 9–10 of decision 2/CMA.5. It contains links to the consolidated list of indicator options, including metadata, where available, produced by the experts and to the reports prepared by each expert group and the technical report prepared by the secretariat, which incorporates the experts’ inputs